2023
DOI: 10.47205/jdss.2023(4-i)17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Safety, Quality and Productivity in Construction Projects

Abstract: Construction is thought to be the most dangerous business due to its unique nature. To reduce risks and boost productivity in the construction industry, quality and safety management is required. The research examines productivity, quality, and safety in terms of their participation in and effects on the execution of building projects. Safety is given first priority throughout construction, with a focus on hazard detection and the prevention of workplace injuries and accidents. There is an examination and prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
4
0
1
Order By: Relevance
“…The strategic implementation of minimizing non-value-adding activities (L1) exhibits a profound economic connection with SDG Target 8.2, which emphasizes the imperative to achieve elevated economic productivity through diversification, technological upgrades, and innovation by efficiently curtailing time-and resource-intensive processes; this is what some research has suggested when matches with lean construction have contributed to heightened economic productivity [33,98].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The strategic implementation of minimizing non-value-adding activities (L1) exhibits a profound economic connection with SDG Target 8.2, which emphasizes the imperative to achieve elevated economic productivity through diversification, technological upgrades, and innovation by efficiently curtailing time-and resource-intensive processes; this is what some research has suggested when matches with lean construction have contributed to heightened economic productivity [33,98].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating continuous improvement (L9) into construction processes also improves safety, health, and community comfort [98]. Moreover, continuous improvement requires robust performance measurement systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Selain itu, keselamtan juga dapat diartikan terbebas dari resiko, kerugian dan kerusakan. [1]- [9]Kecelakaan kerja disebabkan oleh dua faktor, yaitu aspek manusia dan aspek lingkungan dan/atau kombinasi dari keduanya [1] . Aspek manusia berkaitan dengan tindakan manusia yang tidak nyaman, seperti mengabaikan standar operasional prosedur (SOP) yang telah dirintis oleh industri, sedangkan aspek lingkungan umumnya berkaitan dengan cahaya, udara dan suhu, tekanan mental.…”
Section: Pendahuluanunclassified